Ulysses - Joyce, James, 1882-1941 (Salt Lake City, UT : Project Gutenberg, 2003)
"Ulysses" by James Joyce is a modernist novel published in 1922. It chronicles one day in Dublin$1 (BJune 16, 1904$1 (Bfollowing three characters whose experiences mirror Homer's Odyssey. Leopold Bloom parallels Odysseus, his wife Molly echoes Penelope, and Stephen Dedalus reflects Telemachus. Through experimental prose styles and stream of consciousness technique, Joyce explores themes of identity, Irish life, and human consciousness. The novel's complexity, literary allusions, and revolutionary approach to depicting thought have made it one of modernism's most celebrated and debated works. (This is an automatically generated summary.)s
This eBook is based on the pre-1923 print editions.
Wikipedia page on this work: https://en.wikipedia.org/wiki/Ulysses_(novel)
Release date is 2003-07-01
EBook produced by Col Choat.
Keywords: City and town life -- Fiction; Psychological fiction; Domestic fiction; Married people -- Fiction; Male friendship -- Fiction; Dublin (Ireland) -- Fiction; Epic literature; Artists -- Fiction; Jewish men -- Fiction; Alienation (Social psychology) -- Fiction